Aggregation behavior of solubilized meat - Potato protein mixtures. (April 2021) - Ebert, Sandra; Kaplan, Seyma; Brettschneider, Kim; Terjung, Nino; Gibis, Monika; Weiss, Jochen
Abstract: Knowledge on the mixing behavior of meat and plant proteins is of importance for the manufacture of so-called hybrid products, a product category that is becoming of interest to food manufacturers. The aim of this study was to assess the pH-dependent miscibility and aggregation behavior in combinations of solubilized pork meat and potato tuber proteins. Analysis on their individual pH-dependent surface charge and size were followed by a visual and microscopic evaluation of their mixtures. Image analysis was used to obtain separation indices, aggregate areas, and aggregate aspect ratios and FTIR spectra were recorded to obtain insights into secondary structural elements. Net zero charge transition points differed, with a higher value for potato (pH 6.8) compared to meat proteins (pH 5.7). In mixtures, homogeneous solutions (pH 5.8 and 7.0) abruptly changed to phase-separated ones at low (pH 3) to medium (pH 5.5) pH. Here, anisotropic, clustered aggregates at high meat protein contents were exchanged for smaller, irregularly-shaped and sized microstructures at low ones and image analysis suggested a perturbing effect of potato on meat proteins to associate and form fibrous aggregates. The isoelectric point of salt-soluble meat proteins (pH ~ 5.5) was described as defining boundary value for co-solubility or interaction in between individual meat and meat and potato proteins. FTIR results confirmed alterations as a function of mixing ratio and pH. Results indicate that significant textural changes can be expected to occur in hybrid matrices, with plant proteins impeding the structural-self-association of meat proteins. Graphical abstract: Image 1 Highlights: Potato proteins do not act co-solutes but show a complex pH-dependent interaction. Interactions of meat with potato proteins change the aggregation below their p I. Coherent, stranded meat protein networks evolve to irregular, isolated aggregates.